PROGESTERONE ADMINISTRATION TO OVARIECTOMIZED RATS REDUCES WATER AND SALT INTAKE INDUCED BY CENTRAL ADMINISTRATION OF ANGIOTENSIN-II - Dovale, C. F.; Saad, W. A.; Renzi, Antonio [UNESP]; Camargo, GMPA; Queiroz, R. C.; Silveira, JEN; Menani, José Vanderlei [UNESP]; Camargo, LAA (Associação Brasileira de Divulgação Científica (ABRADIC), 1995)
We tested the effects of estradiol, progesterone and testosterone on water and salt intake induced by angiotensin II (ANG II) injected into the third ventricle of female Holtzman rats weighing 250-300 g. The water and salt ingestion observed after 120 min in the control experiments (injection of 0.5 mu l of 0.15 M NaCl into the third ventricle) was 1.6 +/- 0.3 ml (N = 10) and 0.3 +/- 0.1 ml (N = 8) in intact rats, respectively, and 1.4 +/- 0.3 ml (N = 10) and 0.2 +/- 0.1 (N = 8) in ovariectomized rats, respectively. ANG II injected in intact rats (4, 6, 12, 25, and 50 ng, icv, in 0.5 mu l saline) induced an increase in water intake (4.3 +/- 0.6, 5.4 +/- 0.7. 7.8 +/- 0.8, 10.4 +/- 1.2, 11.2 +/- 1.4 ml/120 min, respectively) (N = 43). The same doses of icv ANG II in intact rats increased the 3% NaCl intake (0.9 +/- 0.2; 1.4 +/- 0.3, 2.3 +/- 0.4, 2.2 +/- 0.3. and 2.5 +/- 0.4 ml/120 min, respectively) (N = 42). When administered to ovariectomized rats ANG II induced comparable amounts of water intake (4.0 +/- 0.5, 4.8 +/- 0.6, 6.9 +/- 0.7. 9.6 +/- 0.8, and 10.9 +/- 1.2 ml/120 min, respectively) (N = 43) but there was a significant decrease of 3% NaCl solution ingestion (0.3 +/- 0.1, 0.4 +/- 0.1, 0.8 +/- 0.2, 0.7 +/- 0.2, and 0.6 +/- 0.2 ml/120 min, respectively) (N = 44). Estrogen (50 mu g), progesterone (25 ng), and testosterone (300 mu g) were injected daily into ovariectomized rats for 21 days. Treatment with estrogen decreased the water intake and abolished the saline ingestion induced by icy injection of ANG II (12 ng (2.8 +/- 1.2 and 0.3 +/- 0.1 ml/120 min, respectively) (N = 8). Treatment with progesterone also reduced the water intake (3.3 +/- 0.6 ml/120 min) (N = 8) and abolished the ANG II-induced saline ingestion (0.4 +/- 0.1 ml/120 min) (N = 8), but these effects were not observed with testosterone (6.4 +/- 0.8 and 2.2 +/- 0.3 ml/120 min, respectively) (N = 8). These results indicate that ANG II induces a greater increase in sodium intake in intact female rats than in ovariectomized rats and that estrogen and progesterone impair water and sodium intake in ovariectomized rats.
Keywords: ANGIOTENSIN II; ESTROGEN; PROGESTERONE; TESTOSTERONE; OVARIECTOMY; WATER AND SODIUM INTAKE